1983
DOI: 10.1111/j.1540-6288.1983.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Stock Splits and Market Anomalies

Abstract: Previous studies of market efficiency have reported conflicting results when examining stock splits. Recent studies reporting market inefficiencies have made several methodological improvements, but have failed to control for the possible confounding effects of “unexpected” changes in corporate earnings announced near the stock split event. Stock splits are often issued around the time that firms experience large increases in corporate earnings. Therefore, an explicit treatment of earnings announcements in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This anomaly contradicts the market efficiency hypothesis. Nichols and McDonald (1983) argue that stock splits often coincide with periods of large increases in corporate earnings. Recently, Shue and Townsend (2021) demonstrated that the total return volatility, idiosyncratic volatility and market beta immediately increased by approximately 30% following a 2-for-1 stock split.…”
Section: Stock and Reverse Splitsmentioning
confidence: 99%
“…This anomaly contradicts the market efficiency hypothesis. Nichols and McDonald (1983) argue that stock splits often coincide with periods of large increases in corporate earnings. Recently, Shue and Townsend (2021) demonstrated that the total return volatility, idiosyncratic volatility and market beta immediately increased by approximately 30% following a 2-for-1 stock split.…”
Section: Stock and Reverse Splitsmentioning
confidence: 99%